2003
DOI: 10.1080/00050060310001707217
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive effects of benzodiazepine use: a review

Abstract: Benzodiazepines are among the most widely prescribed psychotropic drugs in the world. According to the Drug Utilisation Subcommittee (1999) in 2001 almost 7 million prescriptions were dispensed through pharmacies in Australia alone (excluding in‐patient hospital prescribing). Benzodiazepines are widely used to treat anxiety, insomnia and panic disorder. The existing literature examining the possible effects of long‐term use of these drugs yields conflicting results. This paper reviews the available research on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 96 publications
(144 reference statements)
1
9
0
1
Order By: Relevance
“…The slower psychomotor performance rates as plasma levels escalated (Table 3) also support this interpretation. Although similar effects have been observed in studies of single doses or a few repeated doses of alprazolam [Laurijssens and Greenblatt, 1996], our study seems to be the only one to examine psychomotor effects over a time span of several weeks [Barker et al, 2003]. Our results reinforce the importance of titrating alprazolam dosage upward gradually-more gradually than in this studyand cautioning patients about possible impairment of psychomotor function even after completing that process.…”
Section: Effects Of Increasing Alprazolam Plasma Levelssupporting
confidence: 86%
“…The slower psychomotor performance rates as plasma levels escalated (Table 3) also support this interpretation. Although similar effects have been observed in studies of single doses or a few repeated doses of alprazolam [Laurijssens and Greenblatt, 1996], our study seems to be the only one to examine psychomotor effects over a time span of several weeks [Barker et al, 2003]. Our results reinforce the importance of titrating alprazolam dosage upward gradually-more gradually than in this studyand cautioning patients about possible impairment of psychomotor function even after completing that process.…”
Section: Effects Of Increasing Alprazolam Plasma Levelssupporting
confidence: 86%
“…However, previous research has suggested that long-term use of benzodiazepines is related to impairments in memory (Birzele, 1992;Curran, 1992;Curran et al, 1994;Massin-Krauss et al, 2002;Mintzer et al, 2001;Tata et al, 1994), attention and concentration (Birzele, 1992;Golombok, 1989;Golombok et al, 1988;Petursson et al, 1983), visuospatial skills (Bergman et al, 1980;Golombok et al, 1988;Sakol & Power, 1988;Tata et al, 1994), and numerous other cognitive functions (Aranko et al, 1983;Bergman et al, 1980Bergman et al, , 1989Birzele, 1992;Brosan et al, 1986;Gorenstein et al, 1994;Lucki et al, 1986;Petursson et al, 1983;Sakol & Power, 1988;Tata et al, 1994;Toenne et al, 1995). [See (Barker et al, 2003) for a recent review.] Some authors have also demonstrated a correlational relationship between benzodiazepine dose and observed deficits (Golombok et al, 1988;Tata et al, 1994).…”
Section: Introductionmentioning
confidence: 96%
“…Prior research, however, has also noted that some of these medication classes may negatively impact neuropsychological functioning. Benzodiazepines in particular have been shown to negatively impact visuospatial ability, speed of processing, and verbal learning (Barker, Jackson, Greenwood, & Crowe, 2003;Curran, 2000;Stewart, 2005). One metaanalysis noted moderate to large effect sizes for all cognitive domains, suggesting significant impairment with long-term benzodiazepine use (Barker, 2004a), with residual cognitive deficits observed for an additional six months (Barker, 2004b).…”
Section: Suggestions For Clinical Practice Andmentioning
confidence: 99%